Stochastic modelling and simulation approaches to analysing enhanced fault tolerance on service‐based software systems. (9th December 2015) - Peng, Kuan‐Li; Huang, Chin‐Yu
Summary: Presently, service‐based software systems (SBSSs) have been heavily deployed to fulfil the functionalities of cloud computing and are widely used in many other application fields. Additionally, maintaining functionality and quality of service levels becomes increasingly important for SBSSs; this is because system operational failures may cause great financial loss to an organization. Fault tolerance (FT) is usually used to provide continuous and reliable system service delivery when failures occur. However, the reliability and performance of FT should be carefully analysed because of the overhead of invoking redundant services. It is also noted that the single point of failure on the FT adjudicators as well as the failure correlation also hamper the benefits of FT in SBSSs. To address these problems, this paper proposes two approaches, the stochastic modelling approach and the simulation approach, for analysing the reliability and performance of generalized FT designs. The first approach is suitable for quick analysis at an early design stage, while the second approach is built on top of the ns‐3 simulator and could be well adapted to incorporate varied uncertainty models in the SBSS environments Extensive experiments and analyses uncover some characteristics that could be useful for SBSS engineers. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Fault tolerance (FT) is a proven technique to provide continuous and reliable service delivery when failures occur. However, the reliability and performance of FT should be carefully analyzed because of the overhead of invoking redundant services and the potential single point of failure in the FT mechanism. To address these problems, this paper proposes two approaches, the stochastic modeling approach and the simulation approach, for analysing the reliability and performance attributes of generalized FT designs in service‐based software systems (SBSSs).